2017
DOI: 10.1007/s00264-017-3566-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of intra-articular tibial plateau fractures: the impact of posterior column fractures

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 26 publications
4
52
0
2
Order By: Relevance
“…There is growing evidence that posterior tibial plateau fractures affect the functional outcome [17, 34]. The reported incidence of posterior tibial plateau fractures ranges from 28.8 to 70.7% [9, 15]. The results of this study found a clear indication that the posterior column fracture was also associated with high morbidity in elderly patients (67.58%), and the PL sub-column (62.69%) was more often involved than the PM sub-column (37.92%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence that posterior tibial plateau fractures affect the functional outcome [17, 34]. The reported incidence of posterior tibial plateau fractures ranges from 28.8 to 70.7% [9, 15]. The results of this study found a clear indication that the posterior column fracture was also associated with high morbidity in elderly patients (67.58%), and the PL sub-column (62.69%) was more often involved than the PM sub-column (37.92%).…”
Section: Discussionmentioning
confidence: 99%
“…Because both classifications provide only two-dimensional information of the fracture, a CT-based three-column classification (TCC) would be a good supplement for evaluation [8]. There were already numerous studies which indicated that implementation of the three-column classification (TCC) might improve the surgical outcome of cases of TPFs [9, 10]. This is the first time that the TCC has been used to evaluate the morphological features of tibial plateau fractures in a large sample size of elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…T 1 WI and T 2 WI can have an elevated signal. T 2 WI showed the best results: A rough edge, thickening and other signs[ 19 ]. According to the relevant statistics, the incidence of joint capsule/articular cavity effusion at the time of fracture of the tibial plateau can reach 90%.…”
Section: Discussionmentioning
confidence: 99%
“…Die Behandlung und Fixierung der posterioren Frakturen wird zunehmend als wichtiger prognostischer Faktor erkannt [3]. Wir konnten beobachten, dass nicht erkannte oder nicht behandelte Frakturen des posterioren Pfeilers und sagittale Achsfehlstellung im Vergleich zu Tibiaplateaufrakturen ohne Beteiligung des posterioren Pfeilers zu signifikant schlechteren Outcome Scores führen [4].…”
Section: Methodsunclassified